Genética do angioedema hereditário: do diagnóstico molecular à caracterização clínica e genética da população brasileira - Veronez, Camila Lopes [UNIFESP] (2016)
Hereditary angioedema (HAE) is a rare autosomal dominant disease in which C1 inhibitor or coagulation factor XII codifying genes are affected, leading to the deregulation of plasma kallikrein-kinin system and increased bradykinin (BK) production. BK causes vasodilation and consequent sporadic localized angioedema without wheals episodes. The duration, severity and frequency of the attacks are widely variable even in kindred. However, there are only few studies concerning the genetic profile of different proteins involved in BK release pathway. The molecular diagnosis was performed by Sanger sequencing of SERPING1 and F12 from 321 Brazilian patients and their relatives. Seventy nine patients presented mutations in SERPING1 (47 women and 32 men), from 21 families, in a total of 19 mutations, 12 of them described for the first time in the literature (c.51+2T>C, c.97_115del19, c.195delG, c.553delG, c.686-1G>A, c.752T>C, c.776_782del7, c.1075_1089del15, c.1104delA, c.1369G>C, c.1376C>A and c.1480C>T). Sixty two patients presented specific mutations in F12 (49 women and 13 men) from 23 families, whereby a partial genetic characterization of HAE Brazilian population was achieved. Pathogenic mutations were absent in 69 symptomatic individuals distributed in 45 families classified as HAE-unknown. In order to search for genetic modulators of HAE symptoms, 15 genes related to BK release pathway were analyzed by nextgeneration sequencing in 87 subjects from different countries. Although no significant genotypephenotype association was found, a list with more than 200 alterations was identified, expanding our knowledge about variation in important genes for HAE pathophysiology and broadening perspectives for future studies.